PELATIHAN PENGUTIPAN DAN CARA MENGHINDARI TINDAKAN PLAGIAT BAGI GURU SMK MUHAMMADIYAH 3 PEKANBARU - Januar Al Amien; Sunanto Sunanto; Desti Mualfah; Baidarus Baidarus; Evans Fuad; Febby Apri Wenando; Soni Soni (Jurnal Pengabdian UntukMu NegeRI, 2018)
Nowadays there are many cases of plagiarism that are becoming our concern. Therefore, the writings on plagiarism are one of the things that is important to be understood by the world of education, to avoid plagiarism. Respect, acknowledge and give credit for the work of others is a necessity in producing writing. We all know that science is developed based on pre-existing science. So that there is no need to hesitate for anyone among Educators when composing scientific papers / written works, mentioning the reference sources. This must be understood as intellectual honesty that will not reduce the weight of our writing. Mention honestly, the source of reference that we use, or quote, so that it will be seen clearly, which parts of our work are ideas or taken from dictionaries, encyclopedias, articles, reports, books, magazines, internet, and others.